Strategi Kepala Sekolah Dalam Menambah Sumber Pembiayaan Pendidikan Melalui Wirausaha Di SD Muhammadiyah 1 Ngawi Tahun Ajaran 2017/ 2018 - fantika fantika fantika (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2018)
This study aims to find out: 1) planning strategies for adding educational funding sources through entrepreneurship, 2) implementing strategies for adding education funding sources through entrepreneurship, 3) evaluating strategies for adding educational funding sources through entrepreneurship, 4) the results of strategies to increase education funding sources through entrepreneurship in Muhammadiyah 1 Elementary School Ngawi 2017/2018 academic year.This study used a descriptive qualitative type, which took place at Muhammadiyah 1 Elementary School in Ngawi held from October 2017 to March 2018. The subjects of this study were the Head of Muhammadiyah 1 Elementary School Ngawi, while the informants were deputy headmasters, teachers, and school treasurers. Methods of collecting data by observation, interviews, and documentation. Test the validity of the data using method triangulation and source triangulation. Data analysis with interactive models starting with data collection, data reduction, data presentation, and conclusion drawing.The results of the study show that: 1) entrepreneurial strategy planning is carried out through the empowerment of existing resources, namely traders, teachers and employees as entrepreneur managers under school management, 2) implementation of entrepreneurial strategies carried out under school management where sellers as catering officers and suppliers , teachers and employees as officers and suppliers of healthy canteens, and event organizers with the aim of other school teachers and the community, 3) evaluation of entrepreneurial strategies namely improving communication with student guardians regarding order of catering payments, controlling student snacks nominal, and planning more mature event organizers and administrative, 4) the results of the entrepreneurial strategy that is able to add educational funding sources, especially from catering entrepreneurs, provide healthy consumption for the school community, and improve school quality. Keywords: Strategy, Source of Education Financing, Entrepreneurship